Effect of Porosity on Mechanical and Electrochemical Properties of Ti–6al–4v Alloy - Paez-Collio, M; Paez-Collio, M; Muñoz-Moena, L; Muñoz-Moena, L (Elsevier Ltd, 2020)
In this work, the effect of porosity on Ti–6Al–4V alloy was studied by using the Archimedes method, BET analysis, ultrasound method, micro-hardness, surface analysis, such as scanning electron microscopy, X-ray powder diffraction and X-ray photoelectron spectroscopy, and electrochemical measurements, such as open circuit potential curves, electrochemical impedance spectroscopy and linear swept voltammetry. Apparent porosity of porous electrodes was close to 31% and 42%, which decreased significantly the elastic modulus. BET analysis revealed that the primary porosity for the porous electrodes was macro-porosity and that the micro- and meso-porosity was increased slightly by exposure. Surface analysis revealed the presence of α-phase and β-phase prior to exposure for bulk and porous electrodes. The impedance response for bulk and porous electrodes were completely different. For bulk electrodes, two time-constants were observed in high and low frequencies ranges, being associated with the formation of an oxide layer and the oxygen reduction reaction taking place at the electrolyte/oxide interface. Whereas the porous electrodes showed a De Levie behavior that was not influenced by porosity and exposure time. Anodic current was not modified by exposure. © 2020 Elsevier Ltd